Kesucian Hati Perspektif Al-Qur’an: Tafsir Bil Ma’tsur Surah Al-A’la Ayat [14-15] - Mubarok, Afriza Syahrul; Quthrunada, Safiatuddina (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This article discusses the bil Ma’tsur interpretation which focuses on interpreting the Qur'an with the Qur'an. The main goal of this research is to explore how the Qur'an views the purity of the heart and how to achieve it. By using direct references from the Qur'an, as well as interrelated and continuous verses, this research is expected to serve as an alternative for those who wish to attain a pure heart. This interpretive method is not the only method of interpretation, but it is the most fundamental one because interpreting verses or chapters in the Qur'an is the best method of interpreting the Qur'an. The method in this research uses library research. In his discourse, the author interprets Surah Al-A’la verses [14-15] with verses that can explain and interpret these verses. Among the verses that interpret Surah Al-A'la are Surah Al-Ankabut [45], Surah Al-Baqarah [43], Surah An-Nisa verse [103], and Surah Al-Isra verse [78]. The results of this research indicate that purity of heart can be achieved through efforts that include the teachings of Islamic law, practices that can be applied within it, which include acts of worship that are mahdzah and ghairu mahdzah. Not only that, congregational prayers, paying zakat, and engaging in dhikr are also included as efforts that can lead to purity of heart. Furthermore, being kind to others and upholding morality also falls into the category of strategies to achieve purity of heart. Whoever is able to attain purity of heart will attain success in this world and the hereafter.